DETERMINATION OF KINEMATIC AND DYNAMIC PARAMETERS IN A COTTON PNEUMOTRANSPORT FAN SHAFT WITH AUTOMATIC CONTROL MECHANISM - Sarimsakov Olimjon Sharipjanovich; Kholbaev Doniyor Juraboevich; Yusupova Maftunakhon Yoqubjon kizi (European Science Publishing, 2024)
Objective. The article describes a simple electrotensometric method of determining the loads of the working bodies of a pneumatic transport device whose energy parameters are controlled for transporting cotton to different distances. As a result of the automatic management of energy indicators, the results of comparing the changes in torque and angular speed values on the air transport fan shaft with the existing system were analyzed. Graphs of the dependence of the torque value on the pneumotransport shaft on the work performance and the dependence of the average value of the angular speed of the pneumotransport shaft on the technological resistance were obtained. Methods. It should be noted that in recent years in cotton ginning enterprises, the use of pneumatic transport system engines with an inverter device has become a demand of the times. Results. Experimental studies of determining the kinematic and dynamic parameters of the pneumotransport fan shaft moving through the proposed system were carried out using the electrical strain gauge method. Conclusion. According to the above research and analysis results, it is possible to reduce energy consumption by 10% by applying inverter devices to the currently used pneumotransport system and adjusting the kinematic and dynamic parameters of the fan shaft.
Keywords: Cotton, pneumatic transport, fan, technological parameter, strain gauge, inverter, electric motor, photoelectric sensor, strain sensor; torque converter, microcontroller, computer, torque, angular speed, amplitude, technological resistance.